A&T Bangladesh Maternal Nutrition Endline Survey 2016: Shasthya Shebika (SS) - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the frontline health worker (FHW) survey conducted to gather data for the Maternal Nutrition Endline as a part of an impact evaluation study of Alive & Thrive (A&T) interventions delivered through Building Resources Across Communities' (BRAC) Essential Health Care (EHC) Program in Bangladesh. A&T is a global initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. In setting its country program goal for Bangladesh in this phase of its study, A&T decided to focus on demonstrating the feasibility of integrating a package of maternal nutrition interventions in a large-scale Maternal, Newborn, and Child Health (MNCH) program. Maternal nutrition should receive equal priority as child nutrition and the A&T program of BRAC already have developed an effective strategy through improving IYCF practices. The objective of this impact evaluation is to assess the impact of integrating nutrition-focused behavior change communication (BCC- interpersonal counselling and mass communication) and community mobilization into BRAC's rural MNCH program on: 1) coverage and utilization of key maternal nutrition interventions; 2) consumption of diversified and adequate amount of foods and micronutrients by pregnant and postpartum women; and 3) early breastfeeding practices. In addition, factors affecting integration of nutrition interventions into a well-established community-based MNCH program platform through frontline health workers and social mobilization were examined. The study used a cluster-randomized design with repeated cross-sectional surveys at baseline and endline. As with the baseline, the endline survey used the same ten subdistricts from four districts (Mymensingh, Rangpur, Kurigram, and Lalmonirhat) in which BRAC's existing rural MNCH project is in place have been selected randomly to provide intensified maternal nutrition interventions. Another 10 subdisctricts/upazilas from the same four districts have been selected as comparison for the evaluation. It was conducted between July–August 2016 by the team from International Food Policy Research Institute (IFPRI), in collaboration with the survey firm, Data Analysis and Technical Assistance, Ltd. (DATA). The endline survey had three components: 1) Household survey for recently delivered women (RDW) and their husbands, 2) Household survey for pregnant women (PW) (with detailed dietary recall), and 3) a Frontline health workers survey (Shasthya Shebika (SS) and Shasthya Kormi (SK)). The frontline health worker (FHW) survey gathered data on service provision by BRAC frontline health workers and other healthcare providers. Data were also gathered on health workers’ time commitment, knowledge and attitude and training related to maternal nutrition, and their job motivation, satisfaction, and supervision. In addition, questions on household assets and mass media habits were included. Two questionnaires were developed for frontline health workers survey—(i) Shasthya Shebika (SS) questionnaire, and (ii) Shasthya Kormi (SK) questionnaire. The data included here are from the survey of Shasthya Shebika (SS).